Canadian wildlife health surveillance—patterns, challenges and opportunities identified by a scoping review - Giacinti, Jolene A.; Jane Parmley, E.; Reist, Mark; Bayley, Daniel; Pearl, David L.; Jardine, Claire M. (Facets (Ottawa), 2022)
The protection and promotion of healthy wildlife populations is emerging as a shared goal among stakeholders in the face of unprecedented environmental threats. Accordingly, there are growing demands for the generation of actionable wildlife health information. Wildlife health surveillance is a connected system of knowledge that generates data on a range of factors that influence health. Canada recently approved the Pan-Canadian Approach to Wildlife Health that describes challenges facing wildlife health programs and provides a path forward for modernizing our approach. This scoping review was undertaken to describe the range of peer-reviewed Canadian wildlife health surveillance literature within the context of the challenges facing wildlife health programs and to provide a quantitative synthesis of evidence to establish baselines, identify gaps, and inform areas for growth. This review describes patterns related to species, location, authorship/funding, objectives, and methodology. Five areas are identified that have the potential to propel the field of wildlife health: representativeness, expanded/diversified collaboration, community engagement, harmonization, and a shift to a solutions-focused and One Health mindset. This scoping review provides a synopsis of 10 years of Canadian wildlife health surveillance, challenges us to envision the future of successful wildlife health surveillance, and provides a benchmark from which we can measure change.